(untitled) (International Seven Journal of Multidisciplinary, 2023)
The COVID-19 pandemic has impacted the economic market and labor contexts around the world. Brazil has suffered one of the worst social and governmental managements of the COVID-19 crisis, forcing workers and organizations to develop coping strategies. This environment can affect both well-being and job performance. Sustainable well-being at work refers to different patterns of relationships between performance and well-being. It may include eudaimonic (eg, Meaning of Work - MOW) or hedonic (eg, emotions) forms of well-being. This study tests the moderating role of job stress recovery on the relationship between flexibility i-ideals and patterns of sustainable well-being at work in Brazilian teleworkers. To this end, we emphasize i-deals as a tool that companies have put into practice to help and manage certain areas of their companies more assertively.